The studio class as a teaching and learning experience in the Apotheke Painting Studio Study Group (Revista Apotheke, 2022)
The text seeks to explain the teaching and learning experiences of the Apotheke Painting Studio Study Group in the field of Art Education amidst the space of the painting studio. It is understood as the main of this proposal, the philosophy of Art as experience, based on John Dewey (2010) and the practices developed in studio classes as a space-time of the exercise of aesthetic experience.
Keywords: studio class; Art and Art Education; aesthetic experience; teaching and learning